2D halide perovskite-based van der Waals heterostructures: contact evaluation and performance modulation. (13th July 2017) - Guo, Yaguang; Saidi, Wissam A; Wang, Qian
Abstract: Halide perovskites and van der Waals (vdW) heterostructures are both of current interest owing to their novel properties and potential applications in nano-devices. Here, we show the great potential of 2D halide perovskite sheets (C4 H9 NH3 )2 PbX4 (X  =  Cl, Br and I) that were synthesized recently (Dou et al 2015 Science 349 1518–21) as the channel materials contacting with graphene and other 2D metallic sheets to form van der Waals heterostructures for field effect transistor (FET). Based on state-of-the-art theoretical simulations, we show that the intrinsic properties of the 2D halide perovskites are preserved in the heterojunction, which is different from the conventional contact with metal surfaces. The 2D halide perovskites form a p-type Schottky barrier (Φh ) contact with graphene, where tunneling barrier exists, and a negative band bending occurs at the lateral interface. We demonstrate that the Schottky barrier can be turned from p-type to n-type by doping graphene with nitrogen atoms, and a low-Φh or an Ohmic contact can be realized by doping graphene with boron atoms or replacing graphene with other high-work-function 2D metallic sheets such as ZT -MoS2, ZT -MoSe2 and H -NbS2 . This study not only predicts a 2D halide perovskite-based FETs, but also enhances the understanding of tuning Schottky barrier height in device applications.